PENGARUH PREVENTIVE MAINTENANCE DAN CORRECTIVE MAINTENANCE TERHADAP RELIABILITY MAINTENANCE PADA MESIN PENGOLAHAN CPO DI PKS PTPN V LUBUK DALAM - Sitohang Zebta Febel Michael; Daulay Nauli Iwan; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of preventive maintenance andcorrective maintenance on reliability maintenance on CPO processing machinesat PKS PTPN V Lubuk Dalam. This research was conducted in Lubuk DalamDistrict, Siak Regency. The sampling method used is the saturated sampletechnique, where the respondents are 84 people who are divided into maintenanceand production sections. The data analysis method used in this study is multiplelinear regression analysis and uses the SPSS version 25.0 application. The resultsof this study indicate that preventive maintenance has an effect on reliabilitymaintenance at PKS PTPN V Lubuk Dalam and corrective maintenance has aneffect on reliability maintenance at PKS PTPN V Lubuk Dalam. From the resultsof the research conducted, the simultaneous regression test showed that thevariable preventive maintenance and corrective maintenance had a significanteffect on reliability maintenance on the CPO processing machine of PKS PTPN VLubuk Dalam. Keywords: Maintenance, Preventive, Corrective, Reliability